Children’s needs and preferences for a child friendly environment in Selangor - Meor Gheda, Mariatul Liza (2017)
Children’s lives are facing huge changes and enormous challenges. They have undergone some massive transformations during the last generation, and will undergo more as they grow up. Global challenges are affecting and will continue to affect their lives. Regardless of this, most of the children still find themselves at odds in their own communities. The neighbourhood environments are the closest for children to explore their well-being. Unfortunately, most of the neighbourhoods’ design does not fulfill their needs and preferences. The aim of this research is to understand children’s perceptions for the outdoor play environment in urban neighbourhood. The research objectives are to analyse the children’s view on their existing urban neighbourhood’s environment, to identify the major barriers of outdoor play activities faced by urban children in Selangor and to identify the children’s needs and preferences that promote outdoor play and create child friendly neighbourhood environments in Selangor. The Zone 3 Shah Alam has been selected for the case study. The data were collected through the participation of children in Child Friendly Neighbourhood Environment (CFNE) Workshop with children age 10 and 11 from Sekolah Kebangsaan Seksyen 7 and Pusat Jagaan Nur Kasih by using focus group interview and children’s drawings, and observation studies. The children’s view on their existing neighbourhood was based on three aspects, which are safety and free movement, space and design, and the participation of children into outdoor play. This study has identified six most important barriers that have become the hindrance for these urban children to have outdoor play activities. The barriers include parents’ constraints, the continuously busy traffic, fear of crime and strangers, the setback of the play space itself, no or less friends, and setting of the housing. Based on children’s need and preferences, this study found three main elements with own characteristics to promote outdoor play and create urban child friendly neighbourhood environment. The elements are safety and nurturing environment, suitability and enjoyability. The results of this study provide the important information for children’s societies, planners, designers and policy makers about children’s view of their current local condition. It is worth pinpointing of children’s preferences on the neighbourhood environment.